2022
DOI: 10.1590/fst.108821
|View full text |Cite
|
Sign up to set email alerts
|

Corosolic acid improves erectile function in metabolic syndrome rats by reducing reactive oxygen species generation and increasing nitric oxide bioavailability

Abstract: To investigate the effect of corosolic acid treatment on erectile function in metabolic syndrome induced rat model. Fifty male 3-week-old SD rats were fed a high fat and high sugar diet. Six months later, metabolic variables were determined. Metabolic syndrome induced erectile function (MED) rats were confirmed by an apomorphine test. Then MED rats were treated with corosolic acid daily by oral gavage for 4 weeks. To evaluate erectile function, intracavernosal pressure (ICP)/mean arterial blood pressure (MAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…ROS play an important role in the body. A lower level of ROS promotes the cellular proliferation, differentiation, tissue regeneration and metabolism, and the high concentrations of ROS induce cell apoptosis and necrosis by oxidative stress (Li et al, 2022). Results of this study showed that, with the increase of TT-ACFM concentration, the fluorescence intensity of ROS gradually increased.…”
Section: Discussionmentioning
confidence: 62%
“…ROS play an important role in the body. A lower level of ROS promotes the cellular proliferation, differentiation, tissue regeneration and metabolism, and the high concentrations of ROS induce cell apoptosis and necrosis by oxidative stress (Li et al, 2022). Results of this study showed that, with the increase of TT-ACFM concentration, the fluorescence intensity of ROS gradually increased.…”
Section: Discussionmentioning
confidence: 62%
“…As a marker, MDA is often used to detect the oxidative stress (Reiter et al, 2014;Ho et al, 2013). There are some antioxidant mechanisms against ROS production and oxidative damage in cells (Li et al, 2022). Cellular antioxidant enzyme, including SOD and CAT, can effectively remove hydrogen peroxide and lipid peroxide, and efficiently detoxify superoxide anion (Mruk et al, 2002).…”
Section: Determination Of Sod Cat Mda Total Protein and Albumin In Serummentioning
confidence: 99%
“…Reactive oxygen species (ROS) could lead to the dysfunction of mitochondria by inhibiting the aerobic respiration process and, resulting in reduced energy expenditure in adipocytes (Wang et al, 2022). In addition, in hypoxic conditions, reactive nitrogen species (RNS) may also be produced during the respiratory chain reaction, and RNS may further lead to the production of reactive species such as reactive aldehydes, malondialdehyde, and 4-hydroxynonenal (Li et al, 2022). Excessive levels of ROS and RNS can cause damage to the adipocyte cellular structure and functions which may induce obesity and metabolic syndrome.…”
Section: Effect Of the Che On Tpc And Rsamentioning
confidence: 99%